Translating community resilience theory into practice: A deliberative Delphi approach. Issue 4 (19th September 2022) - Glass, Jayne; McMorran, Rob; Currie, Margaret; McKee, Annie; Pinker, Annabel; Reed, Mark; Meador, Elliot; Markantoni, Marianna
Abstract: Despite the availability of important theoretical insights that could enhance the resilience of rural communities to complex challenges, there is a paucity of guidance on how to apply these insights in practice. This article therefore presents and assesses a deliberative research process using the Delphi technique to elicit expert knowledge from 22 academics, community practitioners and policymakers working in roles related to community resilience delivery in rural Scotland. The participants co‐produced an operational framework for community resilience, with support from researchers who facilitated the three‐stage, interactive process. The methodology enabled participants to work together in an iterative and inclusive manner, culminating in the collective development of a conceptual framework consisting of eight resilience‐enabling factors and corresponding criteria for monitoring change, which can be used to plan practical action and provide feedback to enable ongoing adaptation. The process also produced an in‐depth understanding of participants' perceptions of rural community resilience, identified key factors that enable or impede rural community resilience, analysed the potential to assess community resilience and explored scale‐related issues. The article explores the implications of this framework for those working to make rural communities more resilient and reflects on the benefits and wider application of this type of research approach for developing shared understandings of complex concepts.